Pengembangan True Random Number Generator berbasis Citra menggunakan Algoritme Kaotis - Dian Arief Risdianto; Bambang Nurcahyo Prastowo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
The security of most cryptographic systems depends on key generation using a nondeterministic RNG. PRNG generates a random numbers with repeatable patterns over a period of time and can be predicted if the initial conditions and algorithms are known. TRNG extracts entropy from physical sources to generate random numbers. However, most of these systems have relatively high cost, complexity, and difficulty levels. If the camera is directed to a random scene, the resulting random number can be assumed to be random. However, the weakness of a digital camera as a source of random numbers lies in the resulting refractive pattern. The raw data without further processing can have a fixed noise pattern. By applying digital image processing and chaotic algorithms, digital cameras can be used to generate true random numbers. In this research, for preprocessing image data used method of floyd-steinberg algorithm. To solve the problem of several consecutive black or white pixels appearing in the processed image area, the arnold-cat map algorithm is used while the XOR operation is used to combine the data and generate the true random number. NIST statistical tests, scatter and histrogram analyzes show the use of this method can produce truly random numbers